Status sistematico del género geobatrachus ruthven 1915 (amphibia: anura) (1979)
The different familial assignations proposed until now for Geobatracbus are compiled. Through the collection of a virtual topotypical series of this monotypic genus, which is endemic of the NW section of the Sierra Nevada de Santa Marta Massif (Departamento del Magdalena, Colombia), a detailed description was made.  67 morphological characters were selected according to the criteria used by Lynch and Heyer in their studies on the philogeny and classification of the leptodactylid frogs, and such characters, compled with the chromosome number (2n =20) were analysed, after initial examination of their meaning in order to ascertain the affinities of the genus. Field work carried on in the region showed that its distribution cover the area of humid forest, with frequent mists, at. 1.750-3.000 m., and pointed also that the species tolerates paraclimacic situations (in plantations of Cupressus sp., and Pinus sp.) , and their habits are exclusively terrestrial and semifossorial.  Among the external characters it can be emphasized the high degree of chromatic individual variation, the absence of xeromorphic adaptations and specialized glandular complexes in the skin, which point towards an adaptation towards a hygrophilic habitat, added to the extreme reduction of the first pedial digit. The skeleton characters, studied through dissection and differential staining, show a generalized type without pronounced reduction in the cranial elements, the occurrence of non-pedicellated teeth in the maxillary arch, the absence of either phragmotic or fossorial adaptations, or epicraneal ornamentation exostosis; a generalized hyoid apparatus; 8 presacral vertebrae without fusion or imbrication, and with specialized transverse processes; no expanded sacral diapophyses, fused talus and calcaneus and only two tarsalia. The T-shaped terminal phalanges might suggest a preadaptation towards an arboreal way of life (or, conversely, an arboreal ancestor); also the full firmisternal condition of the pectoral girdle and the striking clavicular reduction which would show an apparent relationship with the Microhylids. The following muscular characters are noteworthy: M. intermandibularis with medial raphe, the type "s" insertion of the M. adductor mandibularis subexternus, the distal tendon of M. semitendinosus passing ventral to the Mm. graciles, the insertion over the knee of the M. adductor longus, and the absence of an accessory head (or tendon) in the M. glutaeus magnus (an unique condition among the Neobatrachia, presumably due to secondary loss).  In contrast with previous wrong assertions, a direct development (without free larval stages) was confirmed, a condition expected a priori since the eggs are megalecythal and laid in reduced numbers in protected places, in accordance with the scare opportunities for aquatic larval development in mountain environments.  Each of the 68 used characters were codified according to their primitive or derived represented stages, following criteria adopted in the recent literature, with the aim of using principles of numeric taxonomy to at temp the reconstruction of the phylogeny. The possibility that Geobatrachus could belong to the Microhyloidea due to its firmisternal condition, was easily discarded, and the absence of intercalary skeletal pieces in the digits, prevent also any possible close relationship with the Centrolenidae, Hylidae and Pseudidae, although there are no characters (except for the absence of an accessory tendon in the M. glutaeus magnus, regarded as a secondary loss) that might exclude the inclusion of Geobatrachus in the Bufonoidea. No particular characters allow the inclusion of the genus either in the Myobatrachidae or the Heleophrynidae.  The absence of Bidder's organ (which is the only diagnostic difference between the Leptodactylidae and the Bufonidae) eliminate the family Bufonidae from any further consideration, a conclusion that is supported also by experimental cladograms. Distinctive features such as the morphology of the pectoral girdle and the presence of dorsal osteoderms, characteristic of the Brachycephalidae (sensu McDIARMID, 1969) also exclude this family from consideration.   The combinational analysis made through cladograms confirms the presumptive derivation of the Phyllobatinae (= Dendrobatidae) from the Elosiini, and leads to the conclusion that this group might be better regarded as a subfamily of the Leptodactylidae than as a family of their own. Although, in particular the firmisternal condition might suggest affinities of Geobatrachus with the Phyllobatinae, neither this genus or Rhinoderma can be referred to this subfamily. The analysis of the characters of Rhinoderma shows rather conclusively that this genus was derived from the immediate anc estor of the Leptodactylinae or from early members of this group, and under such circumstances Rhinoderma can equally be included in the Leptodactylidae as a representative of a monotypic subfamily. Otherwise, the Leptodactylidae should be divided in several groups of familial hierarchy. However, Geobatrachus widely differs from the Rhinodermatinae, and, as its clearly shown by the cladograms, shows its greater affinity with the Eleutherodactylini, although Geobatrachus is rather outstandingly different from the other genera of this tribe. This condition might be due to the in situ evolution of an early stock, isolated since the Tertiary, that has survived in favored conditions due to climatic equability. Several hypothesis based on the available paleogeographic and paleoclimatic evidence are discussed, in conjunction with the possible fundamental dichotomy of the" Alpha" and" Beta" groups of the genus Eleutberodactylus. With the noticeable exceptions of the genera Euparkerella and Holoaden, the Eleutherodactylini (perhaps originally issued in S. E. Brazil) represent a group of closely related genera, although an exhaustive review of Eleutherodactylus might eventually lead to the splitting of this genus, and to conclusions that agreeing essentially with the conclusions here offered, could otherwise provide basis for a better interpretation of the facts here presented, or even to a reduction of the currently recognized genera for this tribe.  Both, the firmisterny, the loss of the accessory tendon of the M. glutaeus magnus, and the caryotipe (with comparatively reduced number of chromosomes and the lack of acrocentrics), suggest that Geobatrachus represents an extreme line of specialization among the Eleutherodactylini. The evidence afforded by the cladistic analysis gives no support to regard the Eleutherodactylini are derived from Adenomera or an immediate common ancestor with this genus, and so the acquisition of the direct development among the Leptodactylidae seens to have occurred independently at least in two phyletic lines.